2008
DOI: 10.1021/la7031219
|View full text |Cite
|
Sign up to set email alerts
|

Liposome-Templated Supramolecular Assembly of Responsive Alginate Nanogels

Abstract: Nanosized gel particles (nanogels) are of interest for a variety of applications, including drug delivery and single-molecule encapsulation. Here, we employ the cores of nanoscale liposomes as reaction vessels to template the assembly of calcium alginate nanogels. For our experiments, a liposome formulation with a high bilayer melting temperature (Tm) is selected, and sodium alginate is encapsulated in the liposomal core. The liposomes are then placed in an aqueous buffer containing calcium chloride, and the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(38 citation statements)
references
References 31 publications
0
38
0
Order By: Relevance
“…The diffusion of calcium into the liposome interior resulted in alginate gelation within the liposome of size 748 + 280 nm [197]. Another study reported the production of alginate nanogels with a size distribution between 120 and 200 nm [196]. Liposomes were also used as a template to prepare monodisperse PEG hydrogel nanoparticles [20].…”
Section: Liposomes As Templatesmentioning
confidence: 99%
See 1 more Smart Citation
“…The diffusion of calcium into the liposome interior resulted in alginate gelation within the liposome of size 748 + 280 nm [197]. Another study reported the production of alginate nanogels with a size distribution between 120 and 200 nm [196]. Liposomes were also used as a template to prepare monodisperse PEG hydrogel nanoparticles [20].…”
Section: Liposomes As Templatesmentioning
confidence: 99%
“…However, liposomes can be used as templates to produce polymeric nanoparticles and nanogels (figure 12) [20,196,197]. In this approach, the inner compartment of the liposome can be used as the reaction vessel [15,196]. For example, the encapsulation of sodium alginate was performed by the thin-film method.…”
Section: Liposomes As Templatesmentioning
confidence: 99%
“…For example, Haidar and coworkers produced core-shell hybrid nanoparticles by the layer-by-layer assembly of ALG and chitosan on liposomes for the delivery of a growth factor [155]. Conversely, Hong and collaborators used the core of liposomes with a high bilayer melting temperature as reaction vessels to template the assembly of ALG [156]. In this context, ALG was encapsulated in the liposomal core and exposed to a calcium chloride solution at a temperature above the melting point of the bilayer.…”
Section: Alginate Applications In Oral Drug Deliverymentioning
confidence: 99%
“…Then, the liposome was removed with surfactants to give place to 120–200 nm nanoparticles ALG. The process is presented in Figure 14 [156]. As mentioned above, pure drug crystals could also be used to assemble polyelectrolyte layers.…”
Section: Alginate Applications In Oral Drug Deliverymentioning
confidence: 99%
“…4 The intraliposomal aqueous core was gelated by crosslinking of hydrogel polymers for sustained release of the drug. 5,6 However, there has been no systematic study of the effect of intraliposomal viscosity on the flexibility of the lipid vesicle, transfer of molecules through the lipid membrane, and stability of liposomes as a function of the viscosity of the aqueous core of the liposomes. In this study, liposomes with different intraliposomal viscosities were systematically observed to evaluate intraliposomal viscosity as a means to enhance the stability of liposomes and to control the release rate of drugs from liposomes.…”
Section: Introductionmentioning
confidence: 99%